Badanie preferencji klientów biur podróży z wykorzystaniem metod wyborów dyskretnych - Rybicka, Aneta (Preferences analysis of travel agency customers with discrete choice methods, 2006)
In measurement of stated preferences we used the decompositional methods: conjoint analysis and discrete choice methods. In this paper presented an example of discrete choice method application in the study on preferences of travel agency consumers. This research carried out in July and August 2005 on a sample of population of Jelenia Gora. Data were collected especially for this work using questionnaires (394 correctly filled in forms). In the paper a conditional logit model is used to analyse consumer preferences measured against a nominal scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 380-388